Pelatihan Perakitan Mobil Listrik bagi Siswa SMK N 1 Adiwerna - Usman, Mukhamad Khumaidi; Fatkhurozzak, Faqih; Sanjaya, Firman Lukman; Aryanto, Nur Aidi; Akhmadi, Amin Nur; Budi, Sigit Setijo (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
One very important component of an electric car is the battery. Batteries are used as a current source for the entire electrical system and as a place to store electrical energy during the charging process. The power consumption of an electric car with a brushed DC motor drive. To find out the power consumption at a certain constant speed and the battery capacity used, the maximum distance that can be traveled can be calculated. The partner's problem is that there are no activities to assemble electric cars and calculate battery requirements for the power required by electric car. The implementation method uses the method of socialization and training or direct practice. The socialization method is carried out by inviting vocational school students to the mechanical engineering laboratory of Harapan Bersama Polytechnic to be given an explanation and knowledge about the basic principles of electric cars, the main components of electric cars and how to calculate the power required by electric car to be assembled, the activity will be held on June 9 2022 with the result being an increase in students' skills in assembling electric cars. Knowledge of calculating battery power and assembling batteries according to electric car needs, as well as correct electric car installation. The output resulting from this training is that students at SMK N1 Adiwerna have insight into battery circuits and electric car installations.